Temporal variability of the Brazil and the Intermediate Contour current's system at 23 ° S - Laviola da Silva, Matheus (2020)
The Current of Brazil (CB) system is associated with the movement and generation of eddies associated with the current. And, to establish the main chain system o the Brazilian region, a region of enormous economic, biological and geopolitical importance for Brazil. The amount of current in Brazil is mainly inuenced by local training, bathymetry and baroclinic and barotropic instability. The calculation of the volumetric transport of the Brazil Current (CB) and the Intermediate Contour Current (CCI) at 23 ° S is performed in this work using data from reanalysis of the HYCOM-NCODA model. A historical leak series was analyzed using basic statistics and a wavelet transformation. The results of the wavelet spectrum show a well-marked annual cycle in CB and CCI. As well as the dierent variation patterns between CB and CCI, the latter found greater variability in the spectrum.